Novel thermoelectrically convertible molten body and its applications

A controlled crystal growth method using a vertical Bridgman furnace produces a thermoelectric composite with high cubic SrSi2 content, addressing the issues of cracks and impurities in previous methods, achieving high performance and shape-forming capabilities.

JP2024178136APending Publication Date: 2024-12-24TOKYO UNIVERSITY OF SCIENCE +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024093895
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-06-12
Filing Date
2024-06-10
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

Existing methods for synthesizing strontium silicide alloys, such as arc melting and vertical Bridgman methods, result in materials with cracks, voids, and impurities, leading to low thermoelectric conversion performance and difficulty in producing thermoelectric conversion members with desired shapes and sizes.

Method used

A method involving a solid-liquid phase reaction followed by controlled crystal growth from a melt, using a vertical Bridgman furnace, to produce a thermoelectric convertible molten composite with a high content of cubic SrSi2 phase and minimal tetragonal and trigonal phases, enabling direct cutting of thermoelectric conversion members without sintering.

Benefits of technology

The method produces a thermoelectric composite with high thermoelectric conversion performance, mechanical stability, and the ability to form desired shapes, overcoming the limitations of previous methods by ensuring homogeneous and crack-free materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024178136000001_ABST
    Figure 2024178136000001_ABST
Patent Text Reader

Abstract

To provide a novel thermoelectrically convertible molten composite body which is a non-sintered body useful as a thermoelectric conversion material in a low temperature range and has properties that enable cutting out thermoelectric conversion members of a desired shape and size, and a method for manufacturing the same, a thermoelectrically convertible sintered body which is useful as a thermoelectric conversion material in a low temperature range and from which thermoelectric conversion members of a desired shape and size can be cut out, a method for manufacturing the same, a thermoelectric conversion element using the thermoelectrically convertible molten composite body or the thermoelectrically convertible sintered body, and a thermoelectric conversion module including the thermoelectric conversion element.SOLUTION: A thermoelectrically convertible molten composite body according to the present invention is a thermoelectrically convertible molten composite body composed of a strontium silicide polycrystalline body, and as quantitative values obtained by Rietveld analysis of a powder X-ray diffraction pattern, the content of cubic SrSi2 phase is 99.0 mass% or more, and the contents of tetragonal SrSi2 phase and trigonal SrSi2 phase are both less than 0.1 mass%.SELECTED DRAWING: Figure 11
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thermoelectrically convertible molten composite body and a method for producing the same, a thermoelectrically convertible sintered body and a method for producing the same, a thermoelectric conversion element, and a thermoelectric conversion module. [Background technology]

[0002] 2. Description of the Related Art Conventionally, attempts have been made to generate electricity using thermoelectric conversion materials in order to effectively utilize heat (exhaust heat) discharged from various facilities and the like as energy.

[0003] So far, bismuth telluride (Bi2Te3) has been mainly used as a thermoelectric conversion material that shows high thermoelectric conversion performance in the low temperature range of about 0 to 300 degrees C. However, the constituent elements bismuth and tellurium are toxic and have a large environmental impact, and there are problems with the small reserves of the earth's crust.

[0004] In light of this, there is a need for the development of thermoelectric materials that have a low environmental impact, are composed of elements that are abundant in the earth's crust, and exhibit high thermoelectric conversion performance at low temperatures. In recent years, strontium silicide (SrSi2) has been researched as one such thermoelectric material. It is known that SrSi2 exists in cubic, tetragonal, trigonal, and other crystal forms, and of these, only cubic SrSi2 (also known as α-SrSi2) exhibits semiconductor properties and is therefore expected to be used as a thermoelectric material.

[0005] Patent Document 1 describes that a strontium silicide bulk polycrystalline body (sintered body) whose main crystal phase is a cubic SrSi2 phase is obtained by arc melting a composition raw material containing strontium and silicon to obtain a strontium silicide alloy, and then sintering the powder of this strontium silicide alloy. However, the strontium silicide bulk polycrystalline body of Patent Document 1 is characterized by its bulk density and oxygen content, and no measurement data of thermoelectric conversion performance is shown.

[0006] Patent Document 2 also describes that after obtaining a strontium silicide bulk polycrystalline body (sintered body) in the same manner as Patent Document 1, a thin film containing mainly cubic SrSi2 phase and trigonal SrSi2 phase and / or Si was obtained by a sputtering method using this strontium silicide bulk polycrystalline body as a target. Patent Document 2 also shows the thermoelectric conversion performance of the obtained thin film at 300°C.

[0007] Non-Patent Document 1 also describes that a strontium silicide polycrystalline body (melt synthesis body) in which the main crystal phase is the cubic SrSi2 phase is obtained by preparing a molten liquid by heating a composition raw material containing strontium and silicon at a temperature equal to or higher than the melting point of SrSi2 using the generally known vertical Bridgman method, and growing a crystal from the molten liquid.

[0008] In addition, Non-Patent Document 2 describes that a commercially available SrSi2 ingot was crushed, and the resulting powder was sintered at a temperature of 1073 K by a spark plasma sintering method to obtain a strontium silicide sintered body whose main crystal phase was the cubic SrSi2 phase. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] JP 2019-147728 A [Patent Document 2] JP 2019-149523 A [Non-patent literature]

[0010] [Non-Patent Document 1] D. Shiojiri et al., J. Appl. Phys., 129, 115101 (2021) [Non-Patent Document 2] K. Hashimoto et al., J. Appl. Phys., 102, 063703 (2007) Summary of the Invention [Problem to be solved by the invention]

[0011] When strontium silicide alloys are synthesized by the arc melting method as in Patent Documents 1 and 2, the raw materials are rapidly heated locally, and the resulting strontium silicide alloy has many cracks and voids. In addition, since it is difficult to control the temperature in the arc melting method, it is difficult to obtain a strontium silicide alloy whose composition matches that of the raw materials. In fact, in Example 2 of Patent Document 1, although the atomic ratio of strontium to silicon in the raw materials is 1:2, the atomic ratio of strontium to silicon in the resulting strontium silicide alloy is 30:70. Furthermore, the thin film obtained in Patent Document 2 has a maximum power factor at 300°C of 0.46×10 in Example 4. -3 W / mK 2 (film thickness: 1400 nm), which is extremely low. In the case of a thin-film thermoelectric conversion material such as that in Patent Document 2, the generated power is minute, so its applications are thought to be limited.

[0012] On the other hand, when strontium silicide polycrystals are melt-synthesized by the normal vertical Bridgman method as in Non-Patent Document 1, it is possible to obtain strontium silicide polycrystals (melt-synthesized product) that match the composition of the raw material. However, when the present inventors analyzed the strontium silicide polycrystals obtained by the manufacturing method in Non-Patent Document 1, they confirmed that the strontium silicide polycrystals contained about 3 mass% of tetragonal SrSi2 phase (also called β-SrSi2) as a quantitative value obtained by Rietveld analysis of the powder X-ray diffraction pattern. Tetragonal SrSi2 is not a semiconductor but a conductor at a metal level. Non-Patent Document 1 describes that the band gap value of the obtained strontium silicide polycrystals was 13.1 meV, and this low band gap value is thought to be due to the tetragonal SrSi2 phase being contained in the strontium silicide polycrystals. Strontium silicide polycrystals with such a low band gap value are unsuitable as semiconductor thermoelectric conversion materials.

[0013] In addition, Non-Patent Document 2 reports that the power factor of a strontium silicide sintered body manufactured from a commercially available ingot is 1.19 × 10 -3 W / mK 2 However, it is still insufficient for practical use.

[0014] Incidentally, when manufacturing a material (referred to as a thermoelectric conversion member) constituting a thermoelectric conversion part of a thermoelectric conversion element used in a thermoelectric conversion module, it is common to crush a thermoelectric conversion ingot obtained by an arc melting method or a melt synthesis method, sinter it to form a sintered body, and then cut out a thermoelectric conversion member of a desired shape and size from the sintered body. In this regard, if a thermoelectric conversion member can be directly cut out from the thermoelectric conversion ingot itself, the crushing and sintering steps can be omitted, which is convenient. However, in the arc melting method described in Patent Documents 1 and 2, the obtained strontium silicide alloy has many cracks and voids, so it cannot be used to cut out a thermoelectric conversion member. On the other hand, in the melt synthesis method described in Non-Patent Document 1, it is possible to obtain a strontium silicide polycrystalline body (melt synthesis body) without cracks and voids. However, the present inventors confirmed that if the strontium silicide polycrystalline body contains a large amount of tetragonal SrSi2, the cut part collapses when cutting out the thermoelectric conversion member, making it difficult to obtain a thermoelectric conversion member of a desired shape and size.

[0015] The present invention has been made in view of the above, and has an object to provide a novel thermoelectrically convertible molten composite body which is a non-sintered body useful as a thermoelectric conversion material in the low temperature range (approximately 0 to 300°C) and has properties that enable cutting out thermoelectric conversion members of a desired shape and size, and a manufacturing method thereof; a thermoelectrically convertible sintered body which is useful as a thermoelectric conversion material in the low temperature range and enables cutting out thermoelectric conversion members of a desired shape and size, and a manufacturing method thereof; a thermoelectric conversion element using the above thermoelectrically convertible molten composite body or the above thermoelectrically convertible sintered body, and a thermoelectric conversion module including the above thermoelectric conversion element. [Means for solving the problem]

[0016] Specific means for solving the above problems include the following embodiments. <1> A thermoelectric convertible molten composite body composed of a strontium silicide polycrystal, A thermoelectric convertible molten composite body having a cubic SrSi2 phase content of 99.0 mass% or more, and a tetragonal SrSi2 phase content of less than 0.1 mass%, as determined by Rietveld analysis of a powder X-ray diffraction pattern.

[0017] <2> The Si content is less than 0.1% by mass as determined by Rietveld analysis of the powder X-ray diffraction pattern. <1> The thermoelectric convertible molten composite material according to claim 1.

[0018] <3> The Sr content is less than 0.1% by mass as determined by Rietveld analysis of the powder X-ray diffraction pattern. <1> or <2> The thermoelectric convertible molten composite material according to claim 1.

[0019] <4> The power factor at 310K is 2.50×10 -3 W / mK 2 That's all. <1> ~ <3> The thermoelectric convertible molten composite material according to any one of claims 1 to 4.

[0020] <5> The band gap is 45.0 meV or more. <1> ~ <4> The thermoelectric convertible molten composite material according to any one of claims 1 to 4.

[0021] <6> A thermoelectric convertible sintered body made of a strontium silicide polycrystalline body, A thermoelectric conversion sintered body having a cubic SrSi2 phase content of 99.0 mass% or more, and a tetragonal SrSi2 phase content of less than 0.1 mass%, as determined by Rietveld analysis of a powder X-ray diffraction pattern.

[0022] <7> <1> ~ <5> 1. The thermoelectric convertible molten synthetic body according to claim 1 , which is sintered. <6> The thermoelectric conversion sintered body according to claim 1.

[0023] <8> The Si content is less than 0.8% by mass as determined by Rietveld analysis of the powder X-ray diffraction pattern. <6> or <7> The thermoelectric conversion sintered body according to claim 1.

[0024] <9> The Sr content is less than 0.1% by mass as determined by Rietveld analysis of the powder X-ray diffraction pattern. <6> ~ <8> 13. The thermoelectric convertible sintered body according to claim 12.

[0025] <10> The power factor at 310K is 2.35×10 -3 W / mK 2 That's all. <6> ~ <9> 13. The thermoelectric convertible sintered body according to claim 12.

[0026] <11> The band gap is 50.0 meV or more. <6> ~ <10> 13. The thermoelectric convertible sintered body according to claim 12.

[0027] <12> <1> ~ <5> The thermoelectric convertible molten composite material according to any one of the preceding claims, or <6> ~ <11> A thermoelectric conversion part constituted by the thermoelectric conversion sintered body according to any one of the above items, A first electrode and a second electrode provided in the thermoelectric conversion unit; A thermoelectric conversion element comprising:

[0028] <13> <12> A thermoelectric conversion module comprising the thermoelectric conversion element according to claim 1.

[0029] <14> <1> ~ <5> A method for producing a thermoelectrically convertible molten composite according to any one of the above, A solid-liquid phase reaction process in which a raw material composition containing strontium and silicon is heated at a temperature of 1000°C or higher but lower than the melting point of SrSi2 to synthesize SrSi2; A melting step of heating the SrSi2 synthesized in the solid-liquid reaction step to obtain a molten liquid; a crystal growing step of growing a crystal from the melt to obtain a strontium silicide polycrystalline body; A method for producing a thermoelectrically convertible molten composite comprising the steps of:

[0030] <15> The atomic ratio of strontium to silicon in the raw composition is 33.0:67.0 to 34.5:65.5. <14> A method for producing the thermoelectric convertible molten composite material described in claim 1.

[0031] <16> In the crystal growth step, the temperature of the molten liquid is decreased at a rate of 0.223 to 4.72°C / h until the temperature of the molten liquid reaches 1100°C, and after the temperature of the molten liquid reaches 1100°C, the temperature of the molten liquid is decreased at a rate of 0.494 to 10.38°C / h until the temperature of the molten liquid reaches 1000°C. <14> or <15> A method for producing the thermoelectric convertible molten composite material described in claim 1.

[0032] <17> The solid-liquid phase reaction step, the melting step, and the crystal growing step are carried out using a vertical Bridgman furnace; <14> ~ <16> 13. A method for producing the thermoelectric convertible molten composite body according to claim 12.

[0033] <18> <14> ~ <17> 13. A method for producing a thermoelectrically convertible sintered body, comprising a sintering step of sintering a thermoelectrically convertible molten synthetic body obtained by the method for producing a thermoelectrically convertible sintered body according to any one of claims 1 to 12. Effect of the Invention

[0034] According to the present invention, it is possible to provide a novel thermoelectrically convertible molten composite body and a method for producing the same, a novel thermoelectrically convertible sintered body and a method for producing the same, a thermoelectric conversion element using the above-mentioned thermoelectrically convertible molten composite body or the above-mentioned thermoelectrically convertible sintered body, and a thermoelectric conversion module including the above-mentioned thermoelectric conversion element. [Brief description of the drawings]

[0035] [Figure 1] FIG. 1 illustrates an example of a vertical Bridgman furnace. [Diagram 2] FIG. 1 is a diagram showing the movable range (0 mm to 200 mm) of the heating part of a vertical Bridgman furnace. [Diagram 3] FIG. 2 is a diagram showing an example of a sintering apparatus. [Figure 4] FIG. 2 is a diagram illustrating an example of a thermoelectric conversion module. [Diagram 5] FIG. 13 is a diagram illustrating another example of a thermoelectric conversion module. [Figure 6] FIG. 1 is a diagram showing the relationship between the position (0 mm-200 mm) of the heating part of a vertical Bridgman furnace and the temperature directly below the crucible. [Figure 7A] FIG. 2 shows the powder X-ray diffraction patterns of the samples obtained from the ingot of Example 1. [Figure 7B] FIG. 2 shows the powder X-ray diffraction patterns of the samples obtained from the ingot of Example 1. [Figure 8A] FIG. 1 shows the powder X-ray diffraction patterns of the samples obtained from the ingot of Example 2. [Figure 8B] FIG. 1 shows the powder X-ray diffraction patterns of the samples obtained from the ingot of Example 2. [Figure 9] 1 is a graph showing the relationship between temperature and Seebeck coefficient for the test pieces obtained from the ingots of Examples 1 and 2 and the test piece obtained from the sintered body of Example 3. [Figure 10] 1 is a graph showing the relationship between temperature and electrical conductivity in the test pieces obtained from the ingots of Examples 1 and 2 and the test piece obtained from the sintered body of Example 3. [Figure 11] 1 is a graph showing the relationship between temperature and power factor for the test pieces obtained from the ingots of Examples 1 and 2 and the test piece obtained from the sintered body of Example 3. [Figure 12] 13A and 13B are diagrams showing a backscattered electron image and a secondary electron image of the ingot of Example 4 observed with a scanning electron microscope. [Figure 13A] FIG. 1 shows the powder X-ray diffraction patterns of the samples obtained from the ingot of Example 4. [Figure 13B] FIG. 1 shows the powder X-ray diffraction patterns of the samples obtained from the ingot of Example 4. [Figure 14] 13A and 13B are diagrams showing a backscattered electron image and a secondary electron image of the ingot of Example 5 observed with a scanning electron microscope. [Figure 15A] FIG. 1 shows the powder X-ray diffraction patterns of each sample obtained from the ingot of Example 5. [Figure 15B] FIG. 1 shows the powder X-ray diffraction patterns of each sample obtained from the ingot of Example 5. [Figure 16A] FIG. 2 is a diagram showing an X-ray powder diffraction pattern of a sample obtained from the ingot of Comparative Example 1. [Figure 16B] FIG. 2 is a diagram showing an X-ray powder diffraction pattern of a sample obtained from the ingot of Comparative Example 1. [Figure 17] FIG. 2 shows the powder X-ray diffraction patterns of each sample obtained from the ingot of Comparative Example 2. [Figure 18] 1 is a graph showing the relationship between temperature and Seebeck coefficient for test pieces obtained from the ingots of Examples 4 and 5 and Comparative Example 1. [Figure 19] 1 is a graph showing the relationship between temperature and electrical conductivity in test pieces obtained from the ingots of Examples 4 and 5 and Comparative Example 1. [Figure 20] 1 is a graph showing the relationship between temperature and power factor in test pieces obtained from the ingots of Examples 4 and 5 and Comparative Example 1. [Figure 21] FIG. 2 shows optical microscope images of the sintered bodies of Examples 6 to 8 observed with an optical microscope and backscattered electron images observed with a scanning electron microscope. [Figure 22A] FIG. 2 is a diagram showing powder X-ray diffraction patterns of samples obtained from the sintered bodies of Examples 6 to 8. [Figure 22B] FIG. 2 is a diagram showing powder X-ray diffraction patterns of samples obtained from the sintered bodies of Examples 6 to 8. [Figure 23] 1 is a graph showing the relationship between temperature and Seebeck coefficient for test pieces obtained from the sintered bodies of Examples 6 to 8 and Comparative Example 3. [Figure 24] 1 is a graph showing the relationship between temperature and electrical conductivity for test pieces obtained from the sintered bodies of Examples 6 to 8 and Comparative Example 3. [Diagram 25] 1 is a graph showing the relationship between temperature and power factor for test pieces obtained from the sintered bodies of Examples 6 to 8 and Comparative Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0036] Hereinafter, specific embodiments to which the present invention is applied will be described in detail. In this specification, the expression "x to y" using numerical values ​​x and y means "greater than or equal to x and less than or equal to y" unless otherwise specified. In such an expression, when a unit is assigned only to the numerical value y, the unit is also applied to the numerical value x.

[0037] <Thermoelectric conversion melt composite> The thermoelectric convertible molten composite according to this embodiment (hereinafter, simply referred to as "molten composite") is composed of a strontium silicide polycrystalline body whose crystal phase is substantially only a cubic SrSi2 phase. Here, the "molten composite" means a solidified body obtained by heating composition raw materials to prepare a molten liquid, and then growing a crystal while lowering the temperature of the molten liquid.

[0038] The melt synthetic body according to this embodiment has a cubic SrSi2 phase content of 99.0% by mass or more, preferably 99.5% by mass or more, as a quantitative value by Rietveld analysis of a powder X-ray diffraction pattern. In addition, the melt synthetic body according to this embodiment has a tetragonal SrSi2 phase and a trigonal SrSi2 phase content of less than 0.1% by mass, preferably less than the detection limit, as a quantitative value by Rietveld analysis of a powder X-ray diffraction pattern. In addition, the melt synthetic body according to this embodiment has a Sr and Si content of less than 0.1% by mass, preferably less than the detection limit, as a quantitative value by Rietveld analysis of a powder X-ray diffraction pattern. The conditions for the powder X-ray diffraction analysis and the Rietveld analysis are as described in the examples described below.

[0039] In general, when a thermoelectric conversion element is manufactured using a molten composite, if a thermoelectric conversion member is cut directly from the molten composite, the cut portion collapses, making it difficult to obtain a thermoelectric conversion member of a desired shape. For this reason, the molten composite is powdered and then sintered to form a sintered body, from which the thermoelectric conversion member is cut.

[0040] In contrast, the molten composite according to the present embodiment is composed of a strontium silicide polycrystalline body in which the crystal phase is substantially only a cubic SrSi2 phase, and therefore has a homogeneous crystal phase, excellent density, and excellent mechanical properties such as Young's modulus and fracture toughness. Therefore, according to the molten composite according to the present embodiment, a thermoelectric conversion member of a desired shape can be cut out using a wire saw or the like without the cut-out portion collapsing, and as a result, the conventionally performed steps of crushing and sintering can be omitted.

[0041] The thermoelectrically convertible sintered body according to the present embodiment, which will be described later, is obtained by sintering the powder of the molten composite according to the present embodiment, and therefore has minute voids and interfaces between powder particles that do not affect the thermoelectric conversion performance. In contrast, the molten composite according to the present embodiment is obtained by growing crystals from a molten liquid obtained by melting the compositional raw materials, and therefore has no voids and no interfaces between powder particles. This difference can be confirmed by an optical microscope (Nomarski contrast) and a reflected electron microscope.

[0042] In addition, the melt composite according to this embodiment is composed of a strontium silicide polycrystalline body in which the crystal phase is substantially only a cubic SrSi2 phase, and therefore exhibits semiconductor properties. g ) is preferably 45.0 meV or more, more preferably 46.0 meV or more, and even more preferably 47.0 meV or more. g ) is not particularly limited, and is, for example, about 60.0 meV.

[0043] In addition, the melt composite according to this embodiment is composed of a strontium silicide polycrystalline body in which the crystal phase is substantially only the cubic SrSi2 phase, and therefore exhibits high thermoelectric conversion performance in the low temperature range (approximately 0 to 300°C). The power factor of the melt composite according to this embodiment at 310 K is 2.50 × 10 -3 W / mK 2 It is preferable that the value is equal to or greater than 2.60×10 -3 W / mK 2More preferably, it is 2.70×10 or more. -3 W / mK 2 The upper limit of the power factor at 310K is not particularly limited, and is, for example, 3.20 W / mK 2 That's about it.

[0044] The melt composite according to this embodiment also exhibits excellent mechanical properties. The Young's modulus of the melt composite according to this embodiment is preferably 85.0 GPa or more, more preferably 88.0 GPa or more, and even more preferably 90.0 GPa or more. The upper limit of the Young's modulus is not particularly limited, and is, for example, about 100.0 GPa. The fracture toughness value of the melt composite according to this embodiment is 1.0 MPa m 1 / 2 It is preferable that the temperature is 1.2 MPa m or more. 1 / 2 More preferably, it is 1.3 MPa m 1 / 2 The upper limit of the fracture toughness value is not particularly limited, and is, for example, 2.0 MPa m 1 / 2 The Young's modulus and fracture toughness of the molten composite are measured by the method described in the Examples below.

[0045] The inventors have confirmed that the higher the content of the tetragonal SrSi2 phase in the crystal phase of the strontium silicide polycrystal constituting the molten composite, the more likely the molten composite is to be oxidized and deteriorated, and the more difficult it is to cut out the thermoelectric conversion member. This is presumably because tetragonal SrSi2 is more likely to react with moisture. In this regard, the molten composite according to the present embodiment is made of a strontium silicide polycrystal whose crystal phase is substantially only the cubic SrSi2 phase, and therefore has excellent durability and is easy to cut out the thermoelectric conversion member.

[0046] The molten composite according to this embodiment may contain a dopant. Examples of the dopant include p-type dopants such as Ba, Ag, and Ga; and n-type dopants such as N, P, and Sb.

[0047] <Method of manufacturing melt composite> The molten synthetic body according to this embodiment can be produced by a production method (melt synthesis method) including a solid-liquid reaction process in which a composition raw material containing strontium and silicon is heated at a temperature equal to or higher than 1000°C and lower than the melting point of SrSi2 (1121°C) to synthesize SrSi2, a melting process in which the SrSi2 synthesized in the solid-liquid reaction process is heated at a temperature equal to or higher than the melting point of SrSi2 at which SrSi2 does not decompose to obtain a molten liquid, and a crystal growing process in which crystals are grown from the molten liquid to obtain a strontium silicide polycrystalline body.

[0048] In general, when melting and synthesizing an alloy, the composition raw material is heated at a temperature equal to or higher than the melting point of the alloy, and the alloy melt is prepared in one step while synthesizing the alloy, and then the crystal is grown while the temperature of the melt is lowered. That is, it is common to prepare the alloy melt while synthesizing the alloy, and grow the crystal from the melt. In Non-Patent Document 1, the composition raw material is heated at a temperature higher than the melting point of SrSi2 (1121°C), and the SrSi2 melt is prepared while synthesizing SrSi2, and the crystal is grown from the melt. However, according to the study by the present inventors, it has been found that when preparing the SrSi2 melt while synthesizing SrSi2, tetragonal SrSi2 and other impurities are precipitated during crystal growth due to the high temperature during the synthesis of SrSi2.

[0049] In contrast, in the manufacturing method of the melt synthesis product according to the present embodiment, instead of preparing a melt of SrSi2 in one step while synthesizing SrSi2, the process is divided into two steps, a solid-liquid phase reaction step and a melting step, and after completing the synthesis of SrSi2 at a temperature below the melting point of SrSi2, the temperature is raised to a temperature equal to or higher than the melting point of SrSi2 to prepare the melt. According to this manufacturing method, it is possible to obtain a homogeneous strontium silicide polycrystalline body (melt synthesis product) whose crystal phase is substantially only the cubic SrSi2 phase.

[0050] The molten composite produced by the method for producing a molten composite according to the present embodiment exhibits a high band gap value, high thermoelectric conversion performance, and excellent mechanical properties because it is composed of a homogeneous strontium silicide polycrystal whose crystal phase is substantially only a cubic SrSi2 phase. The method for producing a molten composite according to the present embodiment makes it possible to obtain a large molten composite that is industrially useful.

[0051] The composition raw materials used in the method for producing a molten composite according to this embodiment and each step of the production method will be described in detail below.

[0052] [Composition raw materials] The raw material composition used in producing the molten composite according to this embodiment contains strontium and silicon.

[0053] As the strontium in the composition raw material, for example, high purity strontium with a purity of 2N or more (99 mass% or more) is preferably used. Since strontium becomes liquid in the solid-liquid phase reaction process described later, the size of strontium in the composition raw material is not particularly limited. However, from the viewpoint of reaction efficiency in the solid-liquid phase reaction process, it is preferable that the size of strontium in the composition raw material is 3 mm square or less.

[0054] As the silicon in the composition raw material, for example, high purity silicon with a purity of 5N or more (99.999 mass% or more) is preferably used. Since silicon becomes a solid phase in the solid-liquid phase reaction process described later, it is preferable to classify it after powdering it from the viewpoint of reaction efficiency in the solid-liquid phase reaction process. The particle size of the silicon powder is preferably 1 to 100 μm, more preferably 25 to 75 μm.

[0055] The atomic ratio of strontium to silicon in the raw material composition is about 1:2, and preferably 33.0:67.0 to 34.5:65.5.

[0056] [Melting synthesis method] The solid-liquid phase reaction step, melting step, and crystal growth step described below are usually carried out by loading the raw material composition into a crucible, sealing it with a lid, and placing it in a heating furnace.

[0057] The pressure condition during melt synthesis may be atmospheric pressure, but is preferably a positive pressure of about +0.5 to 3.5 kPa. The atmospheric condition during melt synthesis is preferably an inert gas atmosphere such as Ar gas, and more preferably a reducing atmosphere in which an inert gas is mixed with about 3 to 7 volume % of hydrogen gas. By performing melt synthesis in such a reducing atmosphere, the generation of oxides is suppressed, and the ingot after melt synthesis tends to be easily removed from the crucible.

[0058] (Solid-liquid phase reaction process) In the solid-liquid phase reaction process, the raw material is heated to a temperature of 1000° C. or higher and lower than the melting point of SrSi2, and strontium and silicon are reacted to synthesize SrSi2.

[0059] The heating temperature (solid-liquid reaction temperature) in the solid-liquid reaction process needs to be lower than the melting temperature in the subsequent process, but as the heating temperature decreases, tetragonal SrSi2 tends to be generated. Therefore, the heating temperature (solid-liquid reaction temperature) is preferably, for example, 1035 to 1055°C. The heating rate until the solid-liquid reaction temperature is reached is not particularly limited.

[0060] The heating time in the solid-liquid phase reaction step may be any time that allows the solid-liquid phase reaction between strontium and silicon to be completed, and is, for example, preferably 1 to 20 hours, and more preferably 3 to 10 hours.

[0061] (Melting process) In the melting process, the SrSi2 synthesized in the solid-liquid reaction process is heated at a temperature equal to or higher than the melting point of SrSi2 at which SrSi2 does not decompose, to obtain a homogeneous molten liquid without unevenness.

[0062] In order to obtain a homogeneous molten liquid, the heating temperature (melting temperature) in the melting step is, for example, preferably 1121 to 1150° C., and more preferably 1130 to 1135° C. The rate of temperature increase up to the melting temperature is not particularly limited.

[0063] Moreover, the heating time in the melting step may be any time that allows the synthesized SrSi2 to completely melt, and is, for example, preferably 1 to 10 hours, and more preferably 3 to 5 hours.

[0064] (Crystal growth process) In the crystal growth step, the temperature of the molten liquid is lowered to grow crystals from the molten liquid, thereby obtaining a strontium silicide polycrystalline body (melt synthesis body).

[0065] In order to obtain a strontium silicide polycrystalline body whose crystal phase is substantially composed of only the cubic SrSi2 phase, it is preferable to reduce the cooling rate, especially in the initial stage of crystal growth. Specifically, it is preferable to set the cooling rate at 0.223 to 4.72°C / h until the temperature of the molten liquid reaches 1100°C, and to set the cooling rate at 0.494 to 10.38°C / h until the temperature of the molten liquid reaches 1100°C and then reaches 1000°C. After the temperature of the molten liquid reaches 1000°C, it is slowly cooled to room temperature. In this way, by growing the crystal while adjusting the cooling rate, it is possible to obtain a strontium silicide polycrystalline body that does not substantially contain tetragonal SrSi2 and trigonal SrSi2 and has no voids or cracks.

[0066] In the crystal growth process, it is preferable to provide a temperature gradient such that the temperature on the bottom side of the crucible is relatively low and the temperature on the mouth side is relatively high. By providing such a temperature gradient, impurities such as unreacted silicon and Sr2(SiO4) are segregated on the upper side (the mouth side of the crucible), which is the terminal side of the crystal growth, and by removing this portion, a molten composite body made of a high-purity strontium silicide polycrystalline body can be obtained.

[0067] From the viewpoint of easily realizing the above-mentioned temperature gradient, it is preferable that the solid-liquid reaction step, the melting step, and the crystal growth step are all performed using a vertical Bridgman furnace. In the vertical Bridgman furnace, the temperatures of multiple heaters arranged in the vertical direction can be set independently, and a temperature gradient in which the temperature at the bottom is relatively low and the temperature at the top is relatively high can be easily realized. The vertical Bridgman furnace may be one in which the crucible is fixed and the heating part surrounding the crucible is configured to be movable in the vertical direction, or one in which the heating part surrounding the crucible is fixed and the crucible is configured to be movable in the vertical direction.

[0068] Although this may vary depending on the temperature gradient formed in the vertical Bridgman furnace, when a strontium silicide polycrystalline body (a molten composite body) is obtained using a vertical Bridgman furnace in which the heating part is configured to be movable in the vertical direction, it is generally preferable to set the moving speed of the heating part to 0.5 to 7.2 mm / h. In particular, in order to obtain a strontium silicide polycrystalline body that is substantially free of tetragonal SrSi2 and trigonal SrSi2, it is more preferable to set the moving speed of the heating part to 0.5 to 5.5 mm / h, and even more preferably to 1.0 to 4.5 mm / h.

[0069] An example of a vertical Bridgman furnace that can be used in the method for producing a molten composite according to this embodiment is shown in Fig. 1. The vertical Bridgman furnace 1 shown in Fig. 1 includes a furnace body 10 and a heating section 20 that surrounds the furnace body 10.

[0070] The furnace body 10 has a cylindrical quartz glass tube 11 arranged so that its axis direction is vertical, a graphite sample stage 12 arranged inside the quartz glass tube 11 and on which a crucible 30 and a quartz cover 31 are placed, a heat shield plate 13 arranged at the upper inside of the quartz glass tube 11, and a thermocouple 14 for measuring the temperature directly below the crucible. A pressure reduction mechanism for reducing the pressure inside the quartz glass tube 11 and an Ar gas supply mechanism for supplying Ar gas into the quartz glass tube 11 are connected to the quartz glass tube 11.

[0071] The heating section 20 has three heaters 21A, 21B, and 21C arranged vertically around the outer periphery of the quartz glass tube 11, a heat insulating material 22 covering the heaters 21A, 21B, and 21C, and thermocouples 23A, 23B, and 23C for measuring the temperatures of the heaters 21A, 21B, and 21C, respectively. The temperatures of the heaters 21A, 21B, and 21C can be set independently, and when producing a molten composite, a temperature gradient is formed in which the temperature on the lower side (the heater 21C side) is relatively low and the temperature on the upper side (the heater 21A side) is relatively high.

[0072] The vertical Bridgman furnace 1 shown in Fig. 1 is configured so that the heating unit 20 can be moved in the vertical direction. Specifically, the heating unit 20 is configured so that it can be moved in the vertical direction from a position of 0 mm at the bottom end (left side of Fig. 2) to a position of 200 mm at the top end (right side of Fig. 2). By moving the heating unit 20 downward, the temperature of the crucible can be increased, and by moving the heating unit 20 upward, the temperature of the crucible can be decreased.

[0073] <Thermoelectric conversion sintered body> The thermoelectric convertible sintered body according to this embodiment (hereinafter, simply referred to as the "sintered body") is composed of a strontium silicide polycrystalline body whose crystal phase is substantially only a cubic SrSi2 phase, and the above-mentioned present invention fruit The melt composite body according to the embodiment can be obtained by sintering. Since the melt composite body according to the embodiment has excellent sinterability, a dense sintered body without cracks can be obtained.

[0074] The sintered body according to this embodiment, as well as the melt-synthesized body according to this embodiment, has a cubic SrSi2 phase content of 99.0% by mass or more, preferably 99.5% by mass or more, as a quantitative value by Rietveld analysis of the powder X-ray diffraction pattern. In addition, the sintered body according to this embodiment has a tetragonal SrSi2 phase and a trigonal SrSi2 phase content of less than 0.1% by mass, preferably less than the detection limit, as a quantitative value by Rietveld analysis of the powder X-ray diffraction pattern. In addition, the sintered body according to this embodiment has a Sr content of less than 0.1% by mass, preferably less than the detection limit, as a quantitative value by Rietveld analysis of the powder X-ray diffraction pattern. In addition, the sintered body according to this embodiment has a Si content of less than 0.8% by mass, more preferably less than 0.1% by mass, more preferably less than the detection limit, as a quantitative value by Rietveld analysis of the powder X-ray diffraction pattern.

[0075] The sintered body according to this embodiment exhibits semiconductor properties, similar to the melt-synthesized body according to this embodiment. The band gap value (E g ) is preferably 50.0 meV or more, more preferably 51.0 meV or more, and even more preferably 52.0 meV or more. g ) is not particularly limited, and is, for example, about 70.0 meV.

[0076] Moreover, the sintered body according to this embodiment exhibits high thermoelectric conversion performance in the low temperature range (about 0 to 300°C) like the melt-synthesized body according to this embodiment. The power factor of the sintered body according to this embodiment at 310K is 2.35×10 -3 W / mK 2 It is preferable that the value is equal to or greater than 2.40×10 -3 W / mK 2 More preferably, it is 2.45×10 or more. -3 W / mK 2 The upper limit of the power factor at 310K is not particularly limited, and is, for example, 3.00×10 -3 W / mK 2That's about it.

[0077] Moreover, the sintered body according to this embodiment exhibits excellent mechanical properties, similar to the melt-synthesized body according to this embodiment. The Young's modulus of the sintered body according to this embodiment is preferably 80.0 GPa or more, more preferably 85.0 GPa or more, and even more preferably 86.0 GPa or more. There is no particular upper limit to the Young's modulus, and it is, for example, about 100.0 GPa. Moreover, the fracture toughness value of the sintered body according to this embodiment is 1.3 MPa m 1 / 2 It is preferable that the temperature is 1.5 MPa m or more. 1 / 2 More preferably, it is 1.6 MPa m 1 / 2 The upper limit of the fracture toughness value is not particularly limited, and is, for example, 2.0 MPa m 1 / 2 That's about it.

[0078] <Method of manufacturing sintered body> The sintered body according to this embodiment can be produced by a production method including a sintering step of sintering the molten composite body according to the embodiment described above.

[0079] Before sintering, the molten composite according to the present embodiment is preferably powdered and then classified. This tends to produce a dense sintered body without voids. The particle size of the powder of the molten composite is preferably 10 to 100 μm, more preferably 25 to 45 μm.

[0080] For sintering, pressure compression sintering methods such as hot press sintering (HP), hot isostatic pressure sintering (HIP), and spark plasma sintering can be used, with the spark plasma sintering being preferred.

[0081] For example, a jig as shown in Fig. 3 is used for the pressure compression sintering. In sintering, first, the powder of the molten composite is filled into the space surrounded by the graphite die 50 and the graphite punches 51a and 51b shown in Fig. 3. At this time, in order to prevent adhesion, it is preferable to sandwich carbon paper between the powder of the molten composite and the graphite die 50 and the graphite punches 51a and 51b. Thereafter, sintering is performed using a sintering device such as a spark plasma sintering device. Sintering is preferably performed under reduced pressure and in an inert gas atmosphere.

[0082] The sintering pressure in the pressure compression sintering is preferably 60 to 150 MPa. By setting the sintering pressure to 60 MPa or more, it tends to be easier to obtain a sintered body having sufficient density (for example, a relative density of 97% or more with respect to the theoretical density).

[0083] The sintering temperature for the pressure compression sintering is preferably 850 to 950° C. By setting the sintering temperature to 850° C. or higher, a sintered body having sufficient density tends to be obtained. On the other hand, by setting the sintering temperature to 950° C. or lower, damage to the strontium silicide polycrystalline body and the generation of voids are suppressed, and scattering of strontium tends to be prevented.

[0084] <Thermoelectric conversion element> The thermoelectric conversion element according to this embodiment includes a thermoelectric conversion part formed from the molten composite body or sintered body according to this embodiment described above, and a first electrode and a second electrode provided on the thermoelectric conversion part.

[0085] As the thermoelectric conversion section, a thermoelectric conversion member obtained by cutting the molten composite or sintered body according to this embodiment into a desired size using a wire saw or the like can be used. As described above, the molten composite according to this embodiment is homogeneous and has excellent density and mechanical properties (Young's modulus, fracture toughness, etc.), so that the cut-out portion does not collapse and the thermoelectric conversion member can be cut out directly from the molten composite. In addition, since the molten composite according to this embodiment also has excellent sinterability, a sintered body without cracks, excellent density, and excellent mechanical properties (Young's modulus, fracture toughness, etc.) can be obtained. Therefore, the yield when cutting out a thermoelectric conversion member from a sintered body tends to improve.

[0086] The method of forming the first electrode and the second electrode is not particularly limited. Examples include a method of plating the molten composite or sintered body with electroless nickel plating, a method of applying a conductive paste to the molten composite or sintered body and then firing the same, etc. Another example includes a method of laminating a metal powder for forming electrodes, a powder of the molten composite, and a metal powder for forming electrodes in this order, and then obtaining a sintered body by pressure compression sintering, thereby simultaneously forming electrodes during the manufacture of the sintered body.

[0087] <Thermoelectric conversion module> The thermoelectric conversion module according to the present embodiment includes the thermoelectric conversion element according to the present embodiment described above. The configuration of the thermoelectric conversion module according to the present embodiment is not particularly limited, and any configuration such as a π type or a uni-leg type can be adopted.

[0088] An example of the thermoelectric conversion module according to this embodiment is shown in Fig. 4. In the thermoelectric conversion module shown in Fig. 4, electrodes 101 and 111 are provided at the upper ends of an n-type thermoelectric conversion unit 100 and a p-type thermoelectric conversion unit 110 arranged side by side, and electrodes 102 and 112 are provided at the lower ends. The electrodes 101 and 111 are connected to form an integrated electrode, while the electrodes 102 and 112 are configured separately. The molten composite or sintered body according to this embodiment is used for the p-type thermoelectric conversion unit 110, for example.

[0089] 4, the electrodes 101, 111 are heated and heat is dissipated from the electrodes 102, 112, thereby generating a positive temperature difference (Th-Tc) between the electrodes 101, 111 and the electrodes 102, 112, and thermally excited carriers cause the p-type thermoelectric conversion unit 110 to have a higher potential than the n-type thermoelectric conversion unit 100. At this time, a load 130 is connected between the electrodes 102 and 112, causing a current to flow from the p-type thermoelectric conversion unit 110 to the n-type thermoelectric conversion unit 100.

[0090] Another example of the thermoelectric conversion module according to this embodiment is shown in Fig. 5. In the thermoelectric conversion module shown in Fig. 5, an electrode 121 is provided at the upper end of a thermoelectric conversion unit 120, and an electrode 122 is provided at the lower end.

[0091] 5, by heating the electrode 121 side and dissipating heat from the electrode 122 side, a positive temperature difference (Th-Tc) occurs between the electrodes 121 and 122, and the electrode 121 side has a higher potential than the electrode 122 side. At this time, by connecting a load 130 between the electrodes 121 and 122, a current flows from the electrode 121 side to the electrode 122 side. EXAMPLES

[0092] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0093] <Example 1> [Preparation of ingredients] Irregularly shaped strontium (purity 2N, manufactured by Kojundo Chemical Laboratory Co., Ltd.) that had been stored in oil was washed three times with acetone in a glove box with an Ar gas atmosphere, and then cut into 1-3 mm squares.

[0094] In addition, 2-5 mm granular silicon (purity 5N, manufactured by Kojundo Chemical Laboratory Co., Ltd.) and zirconia balls with a diameter of 20 mm were placed in a zirconia container and pulverized at 400 rpm for 2 minutes using a planetary ball mill (PULVERISETTE 7, manufactured by FRITSCH). After pulverization, the mixture was classified using a stainless steel sieve to obtain a powder with a particle size of 75-212 μm.

[0095] [Preparing the crucible] A crucible made of boron nitride (BN) (manufactured by Denka Co., Ltd.) was prepared as the crucible. The internal height of the crucible was 70 mm, and the upper side from the mouth to a position 56.5 mm in the depth direction was approximately cylindrical, while the bottom side had an internal shape that was approximately conical to facilitate the formation of a temperature gradient. The inner diameter of the mouth was 38.75 mm, the inner diameter at the position 56.5 mm in the depth direction from the mouth was 31.2 mm, and the inner diameter of the bottom was 3 mm. In order to prevent a reaction between the strontium melt and the crucible, a mold release agent (Whitey Seven, manufactured by Odec Co., Ltd.) diluted with ethanol was poured into the crucible to coat the inner wall, and the crucible was dried in a drying furnace (80°C, 1 hour or more) and then baked in an electric furnace (1140°C, 10 hours). After that, BN spray (manufactured by Kaken Tech Co., Ltd.) was applied to the entire inner wall.

[0096] An alumina lid (custom-made by Nikkato Corp.) was prepared as the lid for the crucible. The outer surface of the lid was coated with the above-mentioned mold release agent.

[0097] [Melt synthesis of polycrystalline strontium silicide] The heating furnace used was a vertical Bridgman furnace (gas replacement type vertical vacuum heating furnace, custom-made by Heattech Co., Ltd.) with the configuration shown in Figure 1.

[0098] Strontium (20.000g) and silicon (12.822g) were weighed out and loaded into the crucible as raw material composition so that the atomic ratio of strontium to silicon was 33.33:66.67. The crucible was covered with a lid and placed on a graphite sample stand (manufactured by Ueki Corporation), and the entire crucible was covered with a quartz cover. The inside of the heating furnace was then evacuated to a negative pressure of -98kPa or less, and the process of filling with Ar gas until the negative pressure of -50kPa was reached was repeated three times, and finally, Ar gas was filled until the positive pressure of +2.4kPa was reached.

[0099] In the melt synthesis of strontium silicide polycrystalline body, the heating part was fixed at a position 123 mm from the bottom end, and the temperature of the upper heater (heater 21A) and the middle heater (heater 21B) was set to 1130°C, and the temperature of the lower heater (heater 21C) was set to 890°C. The relationship between the position of the heating part (0 mm-200 mm) and the temperature directly below the crucible when the heating part is at the bottom end and at 200 mm when the heating part is at the top end is shown in Figure 6. The temperature directly below the crucible reached 1040°C after 90 minutes. This state was maintained for 10 hours to allow the solid-liquid phase reaction of the composition raw materials to proceed, and SrSi2 was synthesized (solid-liquid phase reaction process).

[0100] Next, the heating part was moved to the bottom end (0 mm position) over 15 minutes. At that time, the temperature directly below the crucible was 1131° C. This state was kept for 5 hours to obtain a molten liquid of SrSi2 (melting process).

[0101] Next, the temperature of the molten liquid was lowered by moving the heating part from the bottom end (0 mm position) to the top end (200 mm position) at a moving speed of 3.6 mm / h, and a crystal was grown from the molten liquid (crystal growth process). The temperature drop rate of the molten liquid was 1.84°C / h on average (minimum: 1.23°C / h, maximum: 2.36°C / h) until it reached 1100°C, and after reaching 1100°C, it was 4.32°C / h on average (minimum: 3.01°C / h, maximum: 5.19°C / h) until it reached 1000°C.

[0102] Thereafter, the temperatures of the upper, middle, and lower heaters were all set to 600° C., and the temperature directly below the crucible was allowed to drop to 600° C. over a period of 5 hours. Furthermore, the temperatures of the upper, middle, and lower heaters were all set to 25° C., and the temperature directly below the crucible was allowed to drop to 25° C. over a period of 5 hours, after which the ingot was removed from the crucible. No voids were visually observed in the obtained ingot.

[0103] [X-ray powder diffraction analysis and Rietveld refinement] About 1 / 5 of the ingot was cut vertically to the height of the crucible at the top (the mouth of the crucible) where the crystal growth was terminated, using a wire saw to obtain the top sample. The remaining part was cut in half vertically to the height of the crucible using a wire saw to obtain the middle and bottom samples. A portion of each sample was powdered and subjected to powder X-ray diffraction analysis using an X-ray diffractometer (MiniFlex300, Rigaku Corporation) under the following conditions: characteristic X-ray: CuKα ray, tube voltage: 40 kV, tube current: 15 mA, scan speed: 3 deg / min, scan step: 0.02 deg.

[0104] The powder X-ray diffraction patterns of each sample are shown in Figures 7A and 7B. As shown in Figures 7A and 7B, impurities such as Si and Sr2(SiO4) were confirmed in the upper sample, but no impurities were confirmed in the middle and lower samples. This result shows that impurities are segregated on the upper side of the ingot (the end side of the crystal growth).

[0105] Furthermore, the powder X-ray diffraction pattern was subjected to Rietveld analysis. The analysis conditions for the Rietveld analysis are shown in Table 1 below, and the quantitative values ​​obtained by the Rietveld analysis are shown in Table 2 below.

[0106] [Table 1]

[0107] [Table 2]

[0108] As shown in Table 2, the crystal phase of the upper sample contained the Si phase and the Sr2(SiO4) phase, while the crystal phase of the middle and lower samples consisted only of the cubic SrSi2 phase. These middle and lower samples can be the melt composites according to the present embodiment described above.

[0109] [Band gap measurement] Using a Hall measurement device (ResiTest8300, manufactured by Toyo Corporation), the carrier concentration of the lower sample was measured at measurement temperatures of 80 to 400 K, and an Arrhenius plot was made. The band gap value was calculated from the slope of the plot line within the fitting range of 280 to 400 K. As a result, the band gap value (E g ) was 48.0 meV.

[0110] <Example 2> [Melt synthesis of polycrystalline strontium silicide] In Example 2, an ingot was obtained in the same manner as in Example 1, except that the melt synthesis conditions were changed as follows.

[0111] In the melt synthesis of the strontium silicide polycrystalline body, first, the heating part was fixed at a position 106 mm from the bottom end, and the temperature of the upper heater (heater 21A) and the middle heater (heater 21B) was set to 1130°C, and the temperature of the lower heater (heater 21C) was set to 890°C. The temperature directly below the crucible reached 1050°C after 90 minutes. This state was maintained for 10 hours to allow the solid-liquid phase reaction of the composition raw materials to proceed, and SrSi2 was synthesized (solid-liquid phase reaction process).

[0112] Next, the heating part was moved to the bottom end (0 mm position) over 15 minutes. At that time, the temperature directly below the crucible was 1133°C. This state was kept for 5 hours to obtain a molten liquid of SrSi2 (melting process).

[0113] Next, the temperature of the molten liquid was gradually lowered by moving the heating part from the bottom end (0 mm position) to the top end (200 mm position) at a moving speed of 1.08 mm / h, and a crystal was grown from the molten liquid (crystal growth process). The temperature drop rate of the molten liquid was 0.617°C / h on average (minimum: 0.445°C / h, maximum: 0.745°C / h) until it reached 1100°C, and after reaching 1100°C, it was 1.152°C / h on average (minimum: 0.988°C / h, maximum: 1.339°C / h) until it reached 1015°C.

[0114] Thereafter, the temperatures of the upper, middle, and lower heaters were all set to 600° C., and the temperature directly below the crucible was allowed to drop to 600° C. over a period of 5 hours. Furthermore, the temperatures of the upper, middle, and lower heaters were all set to 25° C., and the temperature directly below the crucible was allowed to drop to 25° C. over a period of 5 hours, after which the ingot was removed from the crucible. No voids were visually observed in the obtained ingot.

[0115] [X-ray powder diffraction analysis and Rietveld refinement] About 1 / 5 of the ingot was cut vertically to the height of the crucible at the top (the mouth of the crucible) where the crystal growth was terminated, using a wire saw to obtain an upper sample. The remaining portion was cut in half vertically to the height of the crucible using a wire saw to obtain a middle sample and a lower sample. A portion of each sample was then powdered and subjected to powder X-ray diffraction analysis in the same manner as in Example 1.

[0116] The powder X-ray diffraction patterns of each sample are shown in Figures 8A and 8B. As shown in Figures 8A and 8B, impurities such as Si and Sr2(SiO4) were confirmed in the upper sample, but no impurities were confirmed in the middle and lower samples. This result shows that impurities are segregated on the upper side of the ingot (the end side of the crystal growth).

[0117] Furthermore, Rietveld analysis of the powder X-ray diffraction pattern was performed in the same manner as in Example 1. The quantitative values ​​obtained by the Rietveld analysis are shown in Table 3 below.

[0118] [Table 3]

[0119] As shown in Table 3, the crystal phase of the upper sample contained the Si phase and the Sr2(SiO4) phase, while the crystal phase of the middle and lower samples consisted only of the cubic SrSi2 phase. These middle and lower samples can be the melt composites according to the present embodiment described above.

[0120] [Band gap measurement] The band gap value of the lower sample of Example 2 was measured in the same manner as in Example 1. As a result, the band gap value (E g ) was 49.4 meV.

[0121] <Example 3> [Manufacturing of sintered bodies] In a glove box under an Ar gas atmosphere, a part of the lower sample of Example 1 was pulverized using a mortar. After pulverization, the powder was classified using a stainless steel sieve to obtain a sample powder having a particle size of 25 to 45 μm.

[0122] 3.75 g of sample powder was placed in a space surrounded by a graphite die (manufactured by Ueki Corporation) with an inner diameter of 10.4 mm and two graphite punches (manufactured by Ueki Corporation), one above the other (see Figure 3). Carbon paper was sandwiched between the top and bottom of the powder to prevent it from sticking to the punches. In this state, the powder was pressed at a pressure of 60 MPa using a foot-operated hydraulic press (manufactured by Riken Seiki Co., Ltd.) to produce a green compact.

[0123] Next, the graphite die was placed in a spark plasma sintering apparatus (Ed-PAS III, manufactured by Elenix Co., Ltd.), the press pressure was increased to 100 MPa, and spark plasma sintering was performed under an Ar atmosphere. The temperature conditions during sintering were as follows. First, the temperature was raised from room temperature to 500 ° C. over 1 minute, and then raised to 800 ° C. over 1 minute. Next, the temperature was raised at a temperature increase rate of 30 ° C. / min until it reached the sintering temperature of 920 ° C., and was held at 920 ° C. for 10 minutes. Next, the temperature was lowered at a temperature decrease rate of 50 ° C. / min until it reached 600 ° C., during which the press pressure was gradually reduced to 42 MPa. Then, it was allowed to cool to room temperature. The temperature was measured by measuring the temperature of the graphite die, and a K thermocouple was used from room temperature to 580 ° C., and an infrared radiation thermometer was used at temperatures above that.

[0124] After sintering, the attached carbon paper was removed with sandpaper to obtain a sintered body. The shape of the obtained sintered body was cylindrical (top and bottom were circles with a diameter of 10 mm, and the height was 5 mm).

[0125] <Evaluation of thermoelectric conversion performance> The lower samples of Examples 1 and 2 were cut perpendicular to the height direction of the crucible with a wire saw to obtain a roughly disk-shaped sample with a thickness of 2 mm. Furthermore, a test piece with a size of 2 mm x 2 mm x 7.5 mm was cut from the roughly disk-shaped sample with a wire saw. Moreover, the sintered body of Example 3 was cut perpendicular to the axial direction of the cylinder with a wire saw to obtain a disk-shaped sample with a thickness of 2 mm. Furthermore, a test piece with a size of 2 mm x 2 mm x 7.5 mm was cut from the disk-shaped sample with a wire saw.

[0126] For each of the test pieces in Examples 1 to 3, the Seebeck coefficient and electrical conductivity were measured in the temperature range of 300 to 600 K using a thermoelectric property evaluation device (ZEM-3, manufactured by Advance Riko Co., Ltd.). Then, the power factor was calculated based on the obtained Seebeck coefficient and electrical conductivity. The Seebeck coefficient, electrical conductivity, and power factor of each of the test pieces in Examples 1 to 3 are shown in Figs. 9 to 11. As can be seen from Fig. 11, each of the test pieces in Examples 1 to 3 had high thermoelectric conversion performance in the low temperature range. The power factor at 310 K was 2.736 × 10 for Example 1, and 2.736 × 10 for Example 2. -3 W / mK 2 , and Example 2 is 2.919 × 10 -3 W / mK 2 , and Example 3 is 2.845 × 10 -3 W / mK 2 It was.

[0127] <Example 4> [Melt synthesis of polycrystalline strontium silicide] In Example 4, the crucible for loading the raw material was changed to an alumina crucible (manufactured by Nikkato Corporation) with boron nitride pressed onto its inner surface, the gas filled in the heating furnace was changed to Ar gas containing 5% by volume of hydrogen gas, and the melt synthesis conditions were changed as follows. An ingot was obtained in the same manner as in Example 1.

[0128] In the melt synthesis of the strontium silicide polycrystalline body, the heating unit was fixed at a position 123 mm from the bottom end, and the temperature of the upper heater (heater 21A) and the middle heater (heater 21B) was set to 1130°C, while the temperature of the lower heater (heater 21C) was set to 890°C. The temperature directly below the crucible reached 1035°C after 90 minutes. This state was maintained for 10 hours to allow the solid-liquid phase reaction of the composition raw materials to proceed, and SrSi2 was synthesized (solid-liquid phase reaction process).

[0129] Next, the heating part was moved to the bottom end (0 mm position) over 15 minutes. At that time, the temperature directly below the crucible was 1130° C. This state was kept for 5 hours to obtain a molten liquid of SrSi2 (melting process).

[0130] Next, the temperature of the molten liquid was gradually lowered by moving the heating part from the bottom end (0 mm position) to the top end (200 mm position) at a moving speed of 3.6 mm / h, and a crystal was grown from the molten liquid (crystal growth process). The temperature drop rate of the molten liquid was 1.84°C / h on average (minimum: 1.23°C / h, maximum: 2.36°C / h) until it reached 1100°C, and after reaching 1100°C, it was 4.32°C / h on average (minimum: 3.01°C / h, maximum: 5.19°C / h) until it reached 1000°C.

[0131] Thereafter, the temperatures of the upper, middle, and lower heaters were all set to 600°C, and the temperature directly below the crucible was allowed to drop to 600°C over a period of 5 hours. Furthermore, the temperatures of the upper, middle, and lower heaters were all set to 25°C, and the temperature directly below the crucible was allowed to drop to 25°C over a period of 5 hours, after which the ingot was removed from the crucible. No voids were visually observed in the resulting ingot. A backscattered electron image and a secondary electron image of the resulting ingot observed with a scanning electron microscope (SEM) are shown in FIG. 12.

[0132] [X-ray powder diffraction analysis and Rietveld refinement] About 1 / 5 of the ingot was cut vertically to the height of the crucible at the top (the mouth of the crucible) where the crystal growth was terminated, using a wire saw to obtain an upper sample. The remaining portion was cut in half vertically to the height of the crucible using a wire saw to obtain a middle sample and a lower sample. A portion of each sample was then powdered and subjected to powder X-ray diffraction analysis in the same manner as in Example 1.

[0133] The powder X-ray diffraction patterns of each sample are shown in Figures 13A and 13B. As shown in Figures 13A and 13B, Si was confirmed as an impurity in the upper sample, but no impurities were confirmed in the middle and lower samples. This result shows that the impurities are segregated on the upper side of the ingot (the end side of the crystal growth).

[0134] Furthermore, Rietveld analysis of the powder X-ray diffraction pattern was performed in the same manner as in Example 1. The quantitative values ​​obtained by the Rietveld analysis are shown in Table 4 below.

[0135] [Table 4]

[0136] As shown in Table 4, the crystal phase of the upper sample contained a Si phase, while the crystal phase of the middle and lower samples consisted only of a cubic SrSi2 phase. These middle and lower samples can be the melt composites according to the present embodiment described above.

[0137] [Band gap measurement] The band gap value of the lower sample of Example 4 was measured in the same manner as in Example 1. As a result, the band gap value (E g ) was 49.4 meV.

[0138] [Measurement of Young's modulus and fracture toughness] For the lower sample of Example 4, Young's modulus E was calculated according to the following formula: E=9BG / (3B+G) based on density functional theory (DFT) using Hill's approximation equation. In the formula, G represents the shear modulus (Gpa), and B represents the isotropic bulk modulus (Gpa). In addition, for the lower sample of Example 4, fracture toughness was measured in accordance with the IF method of JIS R 1607:2015. As a result, the Young's modulus of the lower sample of Example 4 was 90.17 GPa, and the fracture toughness was 1.452 MPa m 1 / 2 It was.

[0139] <Example 5> [Melt synthesis of polycrystalline strontium silicide] In Example 5, an ingot was obtained in the same manner as in Example 4, except that the melt synthesis conditions were changed as follows.

[0140] In the melt synthesis of the strontium silicide polycrystalline body, first, the heating part was fixed at a position 106 mm from the bottom end, and the temperature of the upper heater (heater 21A) and the middle heater (heater 21B) was set to 1130°C, and the temperature of the lower heater (heater 21C) was set to 890°C. The temperature directly below the crucible reached 1035°C after 90 minutes. This state was maintained for 10 hours to allow the solid-liquid phase reaction of the composition raw materials to proceed, and SrSi2 was synthesized (solid-liquid phase reaction process).

[0141] Next, the heating part was moved to the bottom end (0 mm position) over 15 minutes. At that time, the temperature directly below the crucible was 1130° C. This state was kept for 5 hours to obtain a molten liquid of SrSi2 (melting process).

[0142] Next, the temperature of the molten liquid was gradually lowered by moving the heating part from the bottom end (0 mm position) to the top end (200 mm position) at a moving speed of 1.08 mm / h, and a crystal was grown from the molten liquid (crystal growth process). The temperature drop rate of the molten liquid was 0.617°C / h on average (minimum: 0.445°C / h, maximum: 0.745°C / h) until it reached 1100°C, and after reaching 1100°C, it was 1.152°C / h on average (minimum: 0.988°C / h, maximum: 1.339°C / h) until it reached 1015°C.

[0143] Thereafter, the temperatures of the upper, middle, and lower heaters were all set to 600°C, and the temperature directly below the crucible was allowed to drop to 600°C over a period of 5 hours. Furthermore, the temperatures of the upper, middle, and lower heaters were all set to 25°C, and the temperature directly below the crucible was allowed to drop to 25°C over a period of 5 hours, after which the ingot was removed from the crucible. No voids were visually observed in the resulting ingot. A backscattered electron image and a secondary electron image of the resulting ingot observed by SEM are shown in FIG. 14.

[0144] [X-ray powder diffraction analysis and Rietveld refinement] About 1 / 5 of the ingot was cut vertically to the height of the crucible at the top (the mouth of the crucible) where the crystal growth was terminated, using a wire saw to obtain an upper sample. The remaining portion was cut in half vertically to the height of the crucible using a wire saw to obtain a middle sample and a lower sample. A portion of each sample was then powdered and subjected to powder X-ray diffraction analysis in the same manner as in Example 1.

[0145] The powder X-ray diffraction patterns of each sample are shown in Figures 15A and 15B. As shown in Figures 15A and 15B, Si was confirmed as an impurity in the upper sample, but no impurities were confirmed in the middle and lower samples. This result shows that the impurities are segregated on the upper side of the ingot (the end side of the crystal growth).

[0146] Furthermore, Rietveld analysis of the powder X-ray diffraction pattern was performed in the same manner as in Example 1. The quantitative values ​​obtained by Rietveld analysis are shown in Table 5 below.

[0147] [Table 5]

[0148] As shown in Table 5, the crystal phase of the upper sample contained a Si phase, but the crystal phase of the middle and lower samples consisted only of a cubic SrSi2 phase. These middle and lower samples can be the melt composites according to the present embodiment described above.

[0149] [Band gap measurement] The band gap value of the lower sample of Example 5 was measured in the same manner as in Example 1. As a result, the band gap value (E g ) was 46.1 meV.

[0150] [Measurement of Young's modulus and fracture toughness] The Young's modulus and fracture toughness value of the lower sample of Example 5 were measured in the same manner as in Example 4. As a result, the Young's modulus of the lower sample of Example 5 was 91.14 GPa, and the fracture toughness value was 1.370 MPa m 1 / 2It was.

[0151] <Comparative Example 1> [Melt synthesis of polycrystalline strontium silicide] In Comparative Example 1, an ingot was obtained in the same manner as in Example 4, except that the atomic ratio of strontium to silicon was changed to 33.8:66.2, the fill gas in the heating furnace was changed to Ar gas, and the melt synthesis conditions were changed as follows:

[0152] In the melt synthesis of strontium silicide polycrystal, the heating unit was fixed at a position 197 mm from the bottom end, and the temperature of the upper heater (heater 21A) was set to 1100°C, the temperature of the middle heater (heater 21B) to 1130°C, and the temperature of the lower heater (heater 21C) to 890°C. The temperature directly below the crucible reached 900°C after 90 minutes. This state was maintained for 3 hours to allow the solid-liquid phase reaction of the composition raw materials to proceed, and SrSi2 was synthesized.

[0153] Next, the heating part was moved to the bottom end (0 mm position) over 15 minutes. At that time, the temperature directly below the crucible was 1130°C. This state was kept for 3 hours to obtain a molten SrSi2 liquid.

[0154] Next, the temperature of the molten liquid was gradually lowered by moving the heating part from the bottom end (0 mm position) to the top end (200 mm position) at a moving speed of 7.2 mm / h, and a crystal was grown from the molten liquid (crystal growth process). The temperature drop rate of the molten liquid was 2.13°C / h on average (minimum: 0.88°C / h, maximum: 3.35°C / h) until it reached 1100°C, and after reaching 1100°C, it was 7.02°C / h on average (minimum: 3.56°C / h, maximum: 9.73°C / h) until it reached 1000°C.

[0155] Thereafter, the temperatures of the upper, middle, and lower heaters were all set to 600° C., and the temperature directly below the crucible was allowed to drop to 600° C. over a period of 5 hours. Furthermore, the temperatures of the upper, middle, and lower heaters were all set to 25° C., and the temperature directly below the crucible was allowed to drop to 25° C. over a period of 5 hours, after which the ingot was removed from the crucible.

[0156] [X-ray powder diffraction analysis and Rietveld refinement] A powdered sample was collected from the lower part (bottom side of the crucible) of the obtained ingot, which is the starting side of the crystal growth. Then, a powder X-ray diffraction analysis was performed in the same manner as in Example 1.

[0157] 16A and 16B show the powder X-ray diffraction patterns of the sample of Comparative Example 1. As shown in Fig. 16A and 16B, tetragonal SrSi2 was confirmed in the sample of Comparative Example 1.

[0158] Furthermore, Rietveld analysis of the powder X-ray diffraction pattern was performed in the same manner as in Example 1. Quantitative values ​​obtained by Rietveld analysis are shown in Table 6 below.

[0159] [Table 6]

[0160] As shown in Table 6, the crystal phase of the sample of Comparative Example 1 contained 1.88 mass % of the tetragonal SrSi2 phase.

[0161] [Band gap measurement] The band gap value of the sample of Comparative Example 1 was measured in the same manner as in Example 1. As a result, the band gap value (E g ) was 30.9 meV.

[0162] <Comparative Example 2> [Melt synthesis of polycrystalline strontium silicide] In Comparative Example 2, an ingot was obtained in the same manner as in Example 4, except that the melt synthesis conditions were changed as follows.

[0163] In melt synthesis of strontium silicide polycrystalline body, first, the heating part was fixed at the lower end (0 mm position), and the temperature of the upper heater (heater 21A) and the middle heater (heater 21B) was set to 1130°C, and the temperature of the lower heater (heater 21C) was set to 890°C. The temperature directly below the crucible reached 1130°C after 90 minutes. This state was maintained for 5 hours, and SrSi2 was synthesized while obtaining a molten liquid of SrSi2.

[0164] Next, the temperature of the melt was gradually lowered by moving the heating part from the bottom end (0 mm position) to the top end (200 mm position) at a moving speed of 3.6 mm / h, and a crystal was grown from the melt. The temperature drop rate of the melt was 1.84°C / h on average (minimum: 1.23°C / h, maximum: 2.36°C / h) until it reached 1100°C, and after reaching 1100°C, it was 4.32°C / h on average (minimum: 3.01°C / h, maximum: 5.19°C / h) until it reached 1000°C.

[0165] Thereafter, the temperatures of the upper, middle, and lower heaters were all set to 600° C., and the temperature directly below the crucible was allowed to drop to 600° C. over a period of 5 hours. Furthermore, the temperatures of the upper, middle, and lower heaters were all set to 25° C., and the temperature directly below the crucible was allowed to drop to 25° C. over a period of 5 hours, after which the ingot was removed from the crucible.

[0166] [X-ray powder diffraction analysis] Powder samples 1 and 2 were collected from two different locations on the lower side (bottom side of the crucible) of the obtained ingot, which is the starting side of the crystal growth. Then, powder X-ray diffraction analysis was performed in the same manner as in Example 1.

[0167] The powder X-ray diffraction patterns of Samples 1 and 2 of Comparative Example 2 are shown in Fig. 17. As shown in Fig. 17, in both Samples 1 and 2, a large amount of tetragonal SrSi2 and other impurities were confirmed.

[0168] <Evaluation of thermoelectric conversion performance> The lower samples of Examples 4 and 5 were cut vertically to the height direction of the crucible with a wire saw to obtain a roughly disk-shaped sample with a thickness of 2 mm. Furthermore, a test piece with a size of 2 mm x 2 mm x 7.5 mm was cut out from the roughly disk-shaped sample using a wire saw. Also, a test piece was cut out in the same manner from the ingot of Comparative Example 1.

[0169] For each of the test pieces of Examples 4 and 5 and Comparative Example 1, the Seebeck coefficient and electrical conductivity were measured in the temperature range of 300 to 600 K using a thermoelectric property evaluation device (ZEM-3, manufactured by Advance Riko Co., Ltd.). Then, the power factor was calculated based on the obtained Seebeck coefficient and electrical conductivity. The Seebeck coefficient, electrical conductivity, and power factor of each of the test pieces of Examples 4 and 5 and Comparative Example 1 are shown in Figs. 18 to 20. As can be seen from Fig. 20, each of the test pieces of Examples 4 and 5 had high thermoelectric conversion performance in the low temperature range. The power factor at 310 K was 2.707 × 10 for Example 4, and 2.707 × 10 for -3 W / mK 2 , and Example 5 is 2.893 × 10 -3 W / mK 2 , and Comparative Example 1 is 2.275 × 10 -3 W / mK 2 It was.

[0170] <Examples 6 to 8> [Manufacturing of sintered bodies] In Examples 6 to 8, a part of the lower sample of Example 5 was used, and a sintered body was obtained in the same manner as in Example 3, except that the temperature conditions during sintering were changed as follows.

[0171] During sintering, the temperature was first raised from room temperature to 500°C over 1 minute, and then raised to 800°C over 1 minute. Next, the temperature was raised at a heating rate of 30°C / min until it reached the sintering temperature of 890°C (Example 6), 920°C (Example 7), or 950°C (Example 8), and each sintering temperature was held for 10 minutes. Next, the temperature was lowered at a heating rate of 50°C / min until it reached 600°C, during which the pressing pressure was gradually reduced to 42MPa. After that, it was allowed to cool to room temperature to obtain a sintered body.

[0172] Optical microscope images and backscattered electron images of the sintered bodies of Examples 6 to 8 observed with an optical microscope and SEM are shown in Fig. 21. As can be seen from Fig. 21, the higher the sintering temperature, the fewer the voids and the higher the adhesion of the grain boundaries.

[0173] [Relative density measurement] The apparent densities of the sintered bodies of Examples 6 to 8 were measured by Archimedes' method. The true densities of the sintered bodies of Examples 6 to 8 were measured by a gas replacement method using a gas pycnometer. The relative densities were calculated from the ratios of the apparent densities to the true densities. As a result, the relative densities of the sintered bodies of Example 6 were 97.6%, Example 7 was 97.7%, and Example 8 was 99.7%.

[0174] [X-ray powder diffraction analysis and Rietveld refinement] The ends of the sintered bodies of Examples 6 to 8 were powderized and subjected to powder X-ray diffraction analysis in the same manner as in Example 1.

[0175] 22A and 22B show the powder X-ray diffraction patterns of the sintered bodies of Examples 6 to 8. As shown in Fig. 22A and 22B, Si was confirmed as an impurity in the sintered body of Example 8, but no impurities were confirmed in the sintered bodies of Examples 6 and 7.

[0176] Furthermore, Rietveld analysis of the powder X-ray diffraction pattern was performed in the same manner as in Example 1. Quantitative values ​​obtained by Rietveld analysis are shown in Table 7 below.

[0177] [Table 7]

[0178] As shown in Table 7, the crystal phase of the sintered body of Example 8 contained a small amount of Si phase, while the crystal phase of the sintered bodies of Examples 6 and 7 consisted only of the cubic SrSi2 phase.

[0179] [Band gap measurement] The band gap values ​​of the sintered bodies of Examples 6 to 8 were measured in the same manner as in Example 1. As a result, the band gap values ​​(Eg ) was 55.8 meV in Example 6, 53.8 meV in Example 7, and 52.6 meV in Example 8.

[0180] [Measurement of Young's modulus and fracture toughness] The Young's modulus and fracture toughness of the sintered bodies of Examples 6 to 8 were measured in the same manner as in Example 4. As a result, the Young's modulus was 86.92 GPa for Example 6, 88.56 GPa for Example 7, and 87.32 GPa for Example 8. The fracture toughness was 1.445 MPa m 1 / 2 , and Example 7 is 1.650 MPa m 1 / 2 , and Example 8 is 1.445 MPa m 1 / 2 It was.

[0181] <Comparative Example 3> [Manufacturing of sintered bodies] In Comparative Example 3, a sintered body was obtained in the same manner as in Example 3, except that Sample 1 of Comparative Example 2 was used.

[0182] <Evaluation of thermoelectric conversion performance> The sintered bodies of Examples 6 to 8 and Comparative Example 3 were cut perpendicular to the axial direction of the cylinder with a wire saw to obtain disk-shaped samples with a thickness of 2 mm. Furthermore, test pieces with dimensions of 2 mm x 2 mm x 7.5 mm were cut out from the disk-shaped samples using the wire saw.

[0183] For each of the test pieces of Examples 6 to 8 and Comparative Example 3, the Seebeck coefficient and electrical conductivity were measured in the temperature range of 300 to 600 K using a thermoelectric property evaluation device (ZEM-3, manufactured by Advance Riko Co., Ltd.). Then, the power factor was calculated based on the obtained Seebeck coefficient and electrical conductivity. The Seebeck coefficient, electrical conductivity, and power factor of each of the test pieces of Examples 6 to 8 and Comparative Example 3 are shown in Figs. 23 to 25. As can be seen from Fig. 25, each of the test pieces of Examples 6 to 8 had high thermoelectric conversion performance in the low temperature range. The power factor at 310 K was 2.401 × 10 for Example 6, and 2.401 × 10 for -3 W / mK 2 , and Example 7 is 2.571 × 10 -3 W / mK 2 , and Example 8 is 2.442 × 10 -3W / mK 2 , and Comparative Example 3 is 1.814 × 10 -3 W / mK 2 It was. [Explanation of symbols]

[0184] 1 Vertical Bridgman Furnace 10 Furnace body 11 Quartz glass tube 12 Graphite sample stand 13 Heat shield 14 Thermocouple 20 Heating section 21A, 21B, 21C Heaters 22 Insulation 23A, 23B, 23C Thermocouples 30 Crucible 31 Quartz cover 50 Graphite Dies 51a, 51b Graphite punch 100 n-type thermoelectric conversion unit 101, 102 electrode 110 p-type thermoelectric conversion unit 111, 112 electrode 120 Thermoelectric conversion unit 121, 122 electrode 130 Load

Claims

1. A thermoelectric convertible molten composite body composed of a strontium silicide polycrystal, The quantitative value obtained by Rietveld analysis of the powder X-ray diffraction pattern was cubic SrSi 2 The content of the tetragonal SrSi phase is 99.0 mass% or more. 2 Phase and trigonal SrSi 2 A thermoelectrically convertible molten composite, each of which has a content of less than 0.1 mass % of each phase.

2. 2. The thermoelectrically convertible molten synthetic body according to claim 1, wherein the Si content is less than 0.1 mass% as a quantitative value by Rietveld analysis of a powder X-ray diffraction pattern.

3. 2. The thermoelectrically convertible molten synthetic body according to claim 1, wherein the Sr content is less than 0.1 mass % as a quantitative value by Rietveld analysis of a powder X-ray diffraction pattern.

4. The power factor at 310K is 2.50 x 10 -3 W / mK 2 The thermoelectric convertible molten composite material according to claim 1 .

5. The thermoelectrically convertible molten composite material according to claim 1, having a band gap of 45.0 meV or more.

6. A thermoelectric convertible sintered body made of a strontium silicide polycrystalline body, The quantitative value obtained by Rietveld analysis of the powder X-ray diffraction pattern was cubic SrSi 2 The content of the tetragonal SrSi phase is 99.0 mass% or more. 2 Phase and trigonal SrSi 2 A thermoelectrically convertible sintered body, in which the content of each of the phases is less than 0.1 mass %.

7. 7. A thermoelectrically convertible sintered body according to claim 6, obtained by sintering the thermoelectrically convertible molten synthetic body according to claim 1.

8. The thermoelectrically convertible sintered body according to claim 6, wherein the Si content is less than 0.8 mass% as a quantitative value by Rietveld analysis of a powder X-ray diffraction pattern.

9. The thermoelectrically convertible sintered body according to claim 6, wherein the Sr content is less than 0.1 mass% as a quantitative value by Rietveld analysis of a powder X-ray diffraction pattern.

10. The power factor at 310K is 2.35×10 -3 W / mK 2 The thermoelectric convertible sintered body according to claim 6 .

11. The thermoelectric convertible sintered body according to claim 6, having a band gap of 50.0 meV or more.

12. A thermoelectric conversion part composed of the thermoelectric convertible molten composite body according to any one of claims 1 to 5 or the thermoelectric convertible sintered body according to any one of claims 6 to 11; A first electrode and a second electrode provided in the thermoelectric conversion unit; A thermoelectric conversion element comprising:

13. A thermoelectric conversion module comprising the thermoelectric conversion element according to claim 12.

14. A method for producing a thermoelectric convertible molten composite according to any one of claims 1 to 5, The raw material containing strontium and silicon is heated to 1000°C or higher. 2 Heating at a temperature below the melting point of SrSi 2 A solid-phase / liquid-phase reaction step of synthesizing The SrSi synthesized in the solid-liquid phase reaction process 2 a melting step of heating the mixture to obtain a molten liquid; a crystal growing step of growing a crystal from the melt to obtain a strontium silicide polycrystalline body; A method for producing a thermoelectrically convertible molten composite comprising the steps of:

15. The method for producing a thermoelectric convertible molten composite according to claim 14, wherein the atomic ratio of strontium to silicon in the raw composition material is 33.0:67.0 to 34.5:65.

5.

16. 15. The method for producing a thermoelectrically convertible molten composite body according to claim 14, wherein in the crystal growth step, the temperature of the molten liquid is decreased at a temperature decreasing rate of 0.223 to 4.72 ° C. / h until the temperature of the molten liquid reaches 1100 ° C., and after the temperature of the molten liquid reaches 1100 ° C., the temperature of the molten liquid is decreased at a temperature decreasing rate of 0.494 to 10.38 ° C. / h until the temperature of the molten liquid reaches 1000 ° C. The method for producing a thermoelectrically convertible molten composite body according to claim 14,

17. The method for producing a thermoelectrically convertible molten composite body according to claim 14, wherein the solid-liquid phase reaction step, the melting step, and the crystal growth step are carried out using a vertical Bridgman furnace.

18. A method for producing a thermoelectrically convertible sintered body, comprising a sintering step of sintering a thermoelectrically convertible molten synthetic body obtained by the method according to claim 14.

Citation Information

Patent Citations

  • Bulk body containing strontium and producing method of the same

    JP2019147728A

  • Thin film including strontium and manufacturing method thereof

    JP2019149523A